Transport route optimization using genetic algorithm - Kho, Evie Siaw Hei. (Universiti Malaysia Sarawak, UNIMAS, 2004)
This project is to develop an interface to assist in solving Travelling Salesman Problem, to produce an optimized route given a number of destinations. Genetic Algorithm, a branch in artificial intelligence, applies the concept of selection, crossover and mutation in genetic discipline, is used as the backend engine in this program to optimize a given route.